The color of law: a forgotten history of how our government segregated America - Rothstein, Richard (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2017)
"Richard Rothstein explodes the myth that America's cities came to be racially divided through de facto segregation--that is, through individual prejudices, income differences, or the actions of private institutions like banks and real estate agencies. Rather, The Color of Law incontrovertibly makes it clear that it was de jure segregation--the laws and policy decisions passed by local, state, and federal governments--that actually promoted the discriminatory patterns that continue to this day"--Jacket.
Keywords: Business History and race